Penyuluhan Penggunaan ITE dan Batasan Batasanya Kepada Siswa Sekolah Menengah Atas - Kusumaningsih, Rila; Luhur, Puntadewa Aji; Fachri, Muhamad; Setiawan, Mohamad Arif; Pantouw, Toar Bastian; Permana, Min Dhani; Pirgiawan, Obi (Insan Kreasi Media, 2024)
The ITE Law or Electronic Information and Transaction Law is a law that regulates electronic information and transactions. The ITE Law was first passed through Law No. 11 of 2008 before finally being revised with Law No. 19 of 2016. The stages of this counseling implementation are carried out for approximately 1 hour. In general, the implementation of activities is: Coordination and communication with the school to obtain a general description of students and identify problems that will be the basis for determining the theme of the activity. School students are one of the largest users of social media from the community, whose age range is 13-20 years. Which psychological condition at that age is still unstable in finding identity. With the ITE law, there are certain rules and restrictions on using social media, including the spread of immoral content, gambling, insults, blackmail / threats; the spread of fake news/hoaxes; personal threats of violence; unlawfully hacking someone else's electronic system; and so on. In addition, there are precautions so that we avoid ITE violations, namely being wise in social media, crosschecking the information obtained, not entering vulnerable personal data on social media, not using sentences that contain elements of sara.